2012
DOI: 10.1007/s10640-012-9569-z
|View full text |Cite
|
Sign up to set email alerts
|

Transport and CO2: Productivity Growth and Carbon Dioxide Emissions in the European Commercial Transport Industry

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…2008-2010. 24 Krautzberger L., Wetzel, H. (2012) analyzed the CO2-sensitive productivity growth of the commercial transport industry in 16 member states of the European Union and in Norway for the period 1995-2006. They found productivity decreasing trend on average.…”
Section: Acknowledgementmentioning
confidence: 99%
“…2008-2010. 24 Krautzberger L., Wetzel, H. (2012) analyzed the CO2-sensitive productivity growth of the commercial transport industry in 16 member states of the European Union and in Norway for the period 1995-2006. They found productivity decreasing trend on average.…”
Section: Acknowledgementmentioning
confidence: 99%
“…To measure the effects of the CO 2 emissions change on US transportation productivity for 2002-2011, the Malmquist environmental productivity index was calculated from a Data Envelopment Analysis (program 2.1) 7 and decomposed into conventional and environmentally sensitive Malmquist productivities and their efficiency and technological components in the Malmquist summary of state means in Table 3. In Table 4, the index from the Malmquist summary of annual means was used to reveal the relationship between CO 2 emissions changes and actual productivity.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, global CO 2 emissions from transport increased by 45% in 1990-2007, and these are projected to increase by approximately 40% from 2007 to 2030 [5] [6]. Hence, the transportation sector is a large and steadily growing source of GHG emissions [7].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, others found that the regulation costs lead to productivity loss. Regulatory effects caused a slight decrease in the overall productivity for the European commercial transport industry from 1995 to 2006 [34]. In order to more explicitly conduct the analysis, we depict the scatter plot that indicates the relationship between environmental regulation and carbon productivity.…”
Section: Changing Trend Analysis Of Environmental Regulation and Carbmentioning
confidence: 99%